ANALYSIS OF NON-PERFORMING LOAN (NPL) HANDLING MECHANISMS IN PJT II EMPLOYEE COOPERATIVES BY BHAKTI RAHARJA - Indah Nurfitria Sari; Santi Pertiwi Hari Sandi; Ery Rosmawati (Jurnal Ekonomi, 2022)
PJT II Karya Bhakti Raharja Employee Cooperative is one of the employee cooperatives under the auspices of BUMN. One of the activities in this cooperative, of course, is savings and loans. In financial institutions, the term bad credit is not something foreign. Bad credit or commonly called Non-Performing Loan is a delay in loan payments by customers. Many factors influence the occurrence of bad loans, for example, economic problems that make customers not smooth in paying their loans. To anticipate things like this, each financial institution has its own mechanism or method of handling it. The purpose of this study was to determine the mechanism for handling bad loans or Non Performing Loans in KBR Cooperatives with a quantitative descriptive approach research method. One of the treatments that the KBR Cooperative can take when a customer has bad credit is by giving a Warning Letter (WL 1,2,3). The calculation of the NPL in the KBR cooperative is 0,47%, which means it is in the “very healthy” category.